Feasibility Analysis of The Content of BIPA Bahasaku Level 1 Textbook Published By Alam Bahasa Indonesia - Maharani, Nur Laila; B. Widharyanto, B. Widharyanto; Nugraha, Setya Tri (Devotion : Journal of Research and Community Service, 2024)
Selecting quality textbook is highly predominant in learning process. There are such diverse standards shuould be taken into consideration by the textbook atuhors as content, language, presentation, and graphics. This article describes the appropriateness of the contents of the BIPA Bahasaku level 1 textbook published by Alam Bahasa Indonesia. This research uses a quantitative approach with descriptive quantitative methods. The data analysis technique is carried out through several stages, namely creating scoring criteria, reading qualitative data results, assessing the suitability of the content, and determining eligibility status. The research results show that from the aspect of its content, this book is suitable for utilization in BIPA learning, although several things need to be corrected and improved, namely the depth of the material, the accuracy of learning activities, and the up-to-date references. Based on the assessment results, the contents of this textbook obtained a percentage of 66,6% in the appropriate category. The assessment includes suitability of Competency Standard and Basic Competencies (completeness, breadth, and depth of material), the accuracy of material (accuracy of concepts, definitions, terms, examples, facts, pictures, diagrams, illustrations, data, questions), and learning support material (suitability to development knowledge, up-to-date features/examples/exercises/references, reasoning, problem-solving, relationships between concepts, communication).